Limitation of Ni-rich layered cathodes in all-solid-state lithium batteries - Yu, Tae-Yeon; Lee, Han-Uk; Lee, Jin Wook; Park, Sung-Min; Lee, In-Su; Jung, Hun-Gi; Sun, Yang-Kook (Royal Society of Chemistry, 2023)
All-solid-state batteries (ASSBs) are among the most promising next-generation battery candidates owing to their high energy density and safe operation, both of which are superior to those of lithium-ion batteries (LIBs). Ni-rich layered cathodes are currently benchmark cathode materials for conventional LIBs owing to their high energy densities. This study evaluates the effects of the chemical composition of Ni-rich cathode materials on their electrochemical performance and elucidates the degradation mechanism in ASSBs featuring sulfide solid electrolyte. With increasing Ni content, the long Li+ diffusion pathway originating from the particle morphology more affected adversely the reversible capacity during the initial cycles. Furthermore, microcracks caused by anisotropic volume changes and interfacial reaction between the cathode and solid electrolyte degrade battery performances. Thus, engineering the morphology of the cathode material is a key challenge to improve the battery performances and develop high-energy-density ASSBs with Ni-rich layered cathodes. The degradation of Ni-rich layered cathodes in all-solid-state lithium batteries is largely due to the morphology of the cathode particles. The degradation of battery performance is aggravated with increasing Ni content of the cathode material.